SAGE: supporting secondary data analysis and expediting knowledge mobilization with linked administrative, service delivery, and research data - Zhang, Yunqi; Lloyd-Jones, Hannah; Jagodzinski, Robert; Barbosa, Poliana; Lau, Jason; Cui, Xinjie (International Journal of Population Data Science, 2018)
Introduction The cultural revolution of data sharing is becoming a global movement. It allows for scientific replication and verification of research results, avoiding research duplication, and enabling greater transparency and knowledge mobilization with a relatively low cost. However, privacy protection and data security are critical concerns for human-subject related data sharing. Objectives and Approach In order to facilitate data sharing and engage various stakeholders to better inform policy and practice while protecting privacy, SAGE (Secondary Analysis to Generate Evidence) was established by PolicyWise for Children and Families. It is a collaborative data repository platform that connects stakeholders through secondary use of data. SAGE was built to link, manage, and share research data, community service data, and administrative data related to health and social well-being. Governance and technical processes are in place to ensure that data depositors are involved in decision-making, and data accessed by collaborators are secured and re-identification risks assessed. Results SAGE has been in operation for over a year. Through engagement with the research and non-profit communities, SAGE now offers ten data assets. Discovery is facilitated through well-documented metadata through NADA and Dataverse. Six new collaborative projects have been initiated through SAGE. SAGE is working actively with local non-profits to liberate data to generate evidence and collaborate with each other on common goals. SAGE has helped these organizations understand the legal and legislative barriers to data sharing, and build the technical capacity to further this goal. Discussions are underway with Alberta public entities on how SAGE can support the linkage and governance processes in the use of administrative data. Conclusion/Implications SAGE is putting the governance processes and security practices in place to fill a need for a facilitated data sharing model for sensitive data. SAGE is supporting the cultural shift towards data sharing and reuse by fostering trust and collaboration among researchers, non-profit and government ministries.